Carbonate chemistry and other variables observed during RV METEOR cruise M187 (ReSEAt) from Walvis Bay, Namibia to Walvis Bay, Namibia - Qiu, Li; Browning, Thomas J; Voß, Daniela; Achterberg, Eric Pieter (PANGAEA, 2025)
Carbonate chemistry parameters (pH, total alkalinity [TA], and partial pressure of CO₂ [pCO₂]) along with other oceanographic variables (temperature, salinity, nitrate [NO₃⁻], chlorophyll a [Chl a], and dissolved oxygen [DO]) were measured during the RV METEOR cruise M187 (ReSEAt; 25 January – 2 March 2023; Walvis Bay, Namibia – Walvis Bay, Namibia) using a suite of sensors . Surface water measurements of TA, pCO₂ and pH were obtained using an in situ total alkalinity analyzer (ISA-TA) with a ~7-minute sampling interval, a pCO₂ sensor (HydroC, 4H-Jena Engineering GmbH, Germany) with a 1-minute interval and a pH sensor (Sunburst Sensors, USA) with a 15-minute interval, respectively. All sensors (ISA-TA, pCO₂, pH, and nitrate) were installed in a 68 L tank positioned on a laboratory sink, which was continuously supplied with underway surface seawater (from a depth of ~5 m) during filament tracking. The water flow rate into the tank was maintained at approximately 30 L/min, enabling rapid turnover and ensuring near-real-time measurement of changing water properties. Sensor deployment and data acquisition followed established protocols as described in Qiu et al. (2023a, 2023b, 2024), Fietzek P., et al. (2014) and Nehir M., et al. (2021). We defined the relative coordinates of each cross-filament section (1 to 12), with –1 and +1 representing the southern and northern boundaries (distance normalized), respectively. These boundaries were determined based on the maximum density gradient on each side. Subsequently, all data were interpolated onto a uniform grid ranging from -6 to 6 with a spacing interval of 0.01. Chl a and dissolved oxygen values were provided by a PocketFerryBox system.
Keywords: Atlantic Ocean; Carbonate chemistry; coastal upwelling; filament